Cancer antigen 125 concentrations in patients on chronic peritoneal dialysis: relationship with dialysis quality and membrane transport properties - Jovanović, Nataša Ž.; Trbojević-Stanković, Jasna B.; Nešić, Dejan M; Obrenović, Radmila Ž.; Boričić, Novica I.; Stojimirović, Biljana B. (Archives of Biological Sciences, 2018)
The aim of this study was to evaluate longitudinal changes in drained dialysate cancer antigen 125 (dCA-125) levels and to assess relationships between dCA-125 and dialysis quality, peritoneal membrane transport rates, dialysate glucose load, peritonitis and use of erythropoiesis stimulating agents (ESA), angiotensin-converting-enzyme inhibitors (ACEi) and statins in patients with end-stage renal failure during the first 6 months of peritoneal dialysis (PD) treatment. This prospective study included 20 patients (11 males and 9 females; mean age 62.90±12.69 years) who were followed-up during the first 6 months of PD using conventional low pH glucose-based dialysis fluids. The concentration of dCA-125 was measured in all patients, and the peritoneal equilibration test (PET), peritoneal dialysis treatment adequacy (Kt/V), normalized protein catabolic rate (nPCR), and total, peritoneal and residual clearances of urea and creatinine were calculated. Information on peritonitis occurrence, the use of ESA, ACEi and statins were collected. Data were analyzed by the Mann-Whitney test, Wilcoxon matched pairs test and Spearman’s rank correlation. The concentration of dCA-125 significantly decreased during the follow-up (p=0.016). After 6 months of PD treatment, the concentration of dCA-125 decreased significantly (p=0.016) in all patients. The decrease was present in all patients, but was statistically significant in patients on ACEi therapy (p=0.006) and in patients not using statins (p=0.005) or ESA (p=0.012). No correlation was found between dCA-125 and glucose load, but a statistically significant negative correlation between dCA-125 and the PET for creatinine was observed (p=0.013). These findings challenge the role of dCA-125 in predicting mesothelial cell integrity in PD patients. https://doi.org/10.2298/ABS170324021J Received: March 24, 2017; Revised: May 7, 2017; Accepted: May 9, 2017; Published onlione: June 12, 2017 How to cite this article: Jovanović NŽ, Trbojević-Stanković JB, Nešić DM, Obrenović RŽ, Boričić NI, Stojimirović BB. Cancer antigen 125 concentrations in patients on chronic peritoneal dialysis: Relationship with dialysis quality and membrane transport properties. Arch Biol Sci. 2018;70(1):13-20.